Panorama of Vienna with view of the Graben, including the home of Herr Trattner and the Pestsäule (plague column) - Prixner, Gottfried, 1746-1819 (engraver):::Creator::::::::::::; Weidmann, F.C. (Franz Carl), 1787-1867 (author):::Contributor:::::::::::: (Austria; Vienna; R. Sammer, Buchhändler beyn Kärntherthore)
Copper engraving of the Graben in Vienna, with numbers indicating the home of Johann Thomas Trattner (1) and the Pestsäule (2), also known as the Dreifaltigkeitssäule